To Compare Neutrophil Lymphocyte Ratio with Other Parameters in Acute Exacerbation of COPD and Stable COPD: A Hospital Based Study - Kailash Sharma; Gajendra Singh; Ummed Singh (Asian Journal of Medical Research, 2020)
Background: White blood cell (WBC) count and its subtypes are also well known systemic inflammatory markers. The ratio of neutrophils to lymphocytes (NLR), which is calculated from complete blood count with differential, is an inexpensive widely available marker of inflammation. The aim of this study to compared the neutrophil lymphocyte ratio with other parameters in acute exacerbation of COPD and stable COPD.Subjects and Methods:A Hospital based comparative study done on 50 Patients with COPD (stable/ exacerbation) attending at Government Medical College, Bharatpur, Rajasthan. While the upper limit of neutrophils count for normal range was set at 8x109/l, the lower limit of lymphocyte count for the normal range was set at 0.9x109/l. NLR was calculated as the ratio of neutrophils to lymphocytes, both of which were obtained from the same automated blood samples for the study.Results:Our study showed that the comparison of mean value of age, BMI & pack years was statistically significant (P=0.0112, P<0.0001 & P=0.0141 respectively) in between groups. The comparison of mean value of NLR was statistical significant (P=0.0009) in between groups. NLR measurement demonstrated a sensitivity and specificity of 40%and 77.14%. PPV and NPV for NLR were 63.64%and 56.25%, and OR and RR were 2.250 and 1.455. A positive correlation was determined between NLR and CRP (r=0.482; p<0.05).Conclusion: NLR, like CRP, both readily available and simple parameters, could also be used as a cost-effective marker of inflammation in AECOPD.